A study of the “Iron Ridge” Mine: an excerpt from When Iron Was King in Dodge County, Wisconsin - (:unkn) unknown (My University, 1994)
Mining began at the Iron Ridge Mine (now commonly called Neda Mine) in 1849. The ore is relatively concentrated (nearly 55% iron by weight) and was easily mined initially because some deposits were surficial and of a loosely-cemented granular structure. In the 1850's Byron H. Kilbourn (twice mayor of Milwaukee) purchased most of the land surrounding a competitor's open pit mine, and in 1864 his own Swedes Iron Co. began underground mining. The period from 1850 to 1890 was a period of intense railroad construction in the United States, so there was a high demand for iron from this mine. Because of its hardness, this iron made some of the best rail in the country. Operating until 1914, the mine produced over 685,000 gross tons of ore. The primary reason that the mine closed, and never reopened, is that the ore has a high phosphorus content which renders it unsuitable in the production of steel. The abandoned Neda Mine, owned by the University of Wisconsin-Milwaukee since 1976, has become one of the largest bat hibernacula in Wisconsin.
Keywords: Neda Mine; history; Iron Ridge Mine